1981
DOI: 10.1007/bf00965041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cytidine diphosphate choline (CDP-choline) on ischemia-induced alterations of brain lipid in the gerbil

Abstract: Brain ischemia was produced in gerbils (Meriones unguiculatus) by the bilateral ligation of the carotid arteries. Definite changes in the energy status of brain demonstrated that carotid occlusion was effective. Five minutes before ligation, an intraventricular injection of either saline or cytidine disphosphate choline (CDP-choline, 0.6 micromol/brain, 3 microliter) was given to groups of animals. Control animals, with and without CDP-choline, together with the ischemic groups, were decapitated directly into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 17 publications
1
45
0
2
Order By: Relevance
“…16 Pretreatment with citicoline attenuated the loss of PtdCho during ischemia (no reperfusion). 17 We have previously shown that citicoline attenuated arachidonic acid release and partially restored phospholipid loss after ischemia/1-day reperfusion. 9,18 Citicoline can increase the synthesis of PtdCho 8 and sphingomyelin 19,20 and has been shown to prevent the activation of phospholipase A 2 .…”
mentioning
confidence: 95%
“…16 Pretreatment with citicoline attenuated the loss of PtdCho during ischemia (no reperfusion). 17 We have previously shown that citicoline attenuated arachidonic acid release and partially restored phospholipid loss after ischemia/1-day reperfusion. 9,18 Citicoline can increase the synthesis of PtdCho 8 and sphingomyelin 19,20 and has been shown to prevent the activation of phospholipase A 2 .…”
mentioning
confidence: 95%
“…Various brain diseases, for example, hypoxia, the ischemia related to strokes or injury, and aging per se affect brain levels of these phospholipids (Alberghina et al, 1981a,b ;Goracci et al ., 1981 ;Wie-383 loch et al ., 1984 ;Abe et al ., 1987 ;Abe and Kogure, 1989) . Evidence has been presented that exogenous CDP-choline or CDP-ethanolamine, which are completely degraded to cytidine plus choline or ethanolamine when administered orally, can reverse these membrane changes (Trovarelli et al ., 1981 ;Dorman et al ., 1983) and thereby perhaps ameliorate the clinical findings associated with the disease (De la Morena, 1991) . The present report provides a neurochemical basis for such effects .…”
mentioning
confidence: 99%
“…Citicoline increases the formation of PtdCho and other phospholipids in brain in vitro as well as in vivo (Lopez-Coviella et al, 1995;Wang and Lee, 2000) and at the same time prevents ischemia-triggered tissue accumulation of FFA (Trovarelli et al, 1981). As discussed in the previous section, these effects should be antiapoptotic and neuroprotective.…”
Section: Neuroprotection By Citicolinementioning
confidence: 89%